Reasons behind sickness presenteeism: insights from four national surveys in Latvia - Lakiša, Svetlana; Gobina, Inese; Vanadziņš, Ivars; Matisāne, Linda (Frontiers in Public Health, 2025)
IntroductionSickness presenteeism—working despite being ill—is influenced by work demands, personal circumstances, and socio-demographic factors. This study investigates the prevalence of sickness presenteeism and its self-reported reasons across socio-demographic groups in Latvia.MethodsData were pooled from four consecutive cross-sectional surveys conducted from 2006 to 2018, representing a sample of 6,368 hired workers. Logistic regression was used to assess associations between presenteeism and socio-demographic variables (gender, age, education, income, and job position), while chi-squared tests examined differences in reasons for presenteeism.ResultsOverall, 11% of respondents reported working while ill in the past year. The most common reasons were a lack of replacement possibilities (27.7%), financial considerations (25.5%), specific work-related aspects (17.4%), and mild illness (14.0%). Significant socio-demographic differences were observed, with gender, income level, and job position influencing the reasons for presenteeism.DiscussionThese findings underscore the need for targeted workplace policies, including strategies to address replacement gaps, financial insecurity, and job-related pressures. Future research should explore cross-national comparisons and the impact of evolving work patterns, such as telework, on presenteeism trends.